(untitled) (Journal of Comparative & International Higher Education, 2021)
The reasons why foreign graduate students studied or study at Japanese research-intensive universities were investigated, based on a questionnaire survey and interviews. According to the questionnaire survey, the main three reasons were that the research or education level of Japanese universities was high, that they liked Japan, and that they got scholarships. Supervisors’ recommendations, positive willingness, Japanese culture, and advantage in promotion also seem to be incentives for acquiring doctorates. These reasons were also mentioned by three Thai interviewees. This study showed that exchange of culture and supervisors was also important in addition to factors known in previous studies. This study also implies international students across borders of more than three nations with strong willingness. It is important for Japanese policymakers to arrange environments so that exchanges of culture and supervisors is actived, and international students can move freely.